Mudslide-caused ecosystem degradation following Wenchuan earthquake 2008 - Ren, Diandong; Wang, J.; Fu, R.; Karoly, D.; Hong, Y.; Leslie, Lance; Fu, C.; Huang, G. (AMERICAN GEOPHYSICAL UNION, 2009)
We have applied a scalable and extensible geo-fluid model (SEGMENT) that considers soil mechanics, vegetation transpiration and root mechanical reinforcement, and hydrological processes to simulate two dimensional maps of the landslides occurrence following the 2008 Wenchuan earthquake. Modeled locations and areas generally agree with observations. The model suggests that the potential energy of earth was lowered by 1.52 × 1015 J by these landslides. With this, the vegetation destroyed transfer ~235 Tg C to the dead respiring pool and transforms 5.54 × 10−2 Tg N into unavailable sediments pools and the atmosphere. The cumulative CO2 release to the atmosphere over the coming decades is comparable to that caused by hurricane Katrina 2005 (~105 Tg) and equivalent to ~2% of current annual carbon emissions from global fossil fuel combustion. The nitrogen loss is twice as much as that released by the 2007 California Fire (~2.5 × 10−2 Tg). A significant proportion of the nitrogen loss (14%) is in the form of nitrous oxide, which can affect the atmospheric ozone layer.